A polymorphism of the interleukin-1 β gene influences survival in pancreatic cancer - Barber, M D (Nature Publishing Group, 2000)
Pro-inflammatory cytokines contribute to the cachexia associated with pancreatic cancer and stimulate the acute phase response which has been associated with shortened survival in such patients. Polymorphisms of cytokine genes may influence their production. The present study examined the effect of a polymorphism of the interleukin (IL)-1b gene upon the inflammatory state and survival in pancreatic cancer. Genomic DNA was obtained from 64 patients with pancreatic cancer and 101 healthy controls. Using the polymerase chain reaction and subsequent TaqI restriction enzyme digestion the subject's genotype for a diallelic polymorphism of the interleukin-1b gene was established. IL-1b production by peripheral blood mononuclear cells and serum C-reactive protein (CRP) levels from patients were also examined and survival noted. Patients homozygous for allele 2 of the IL-1b gene had significantly shorter survival than other groups (P = 0.0001). These patients also exhibited higher IL-1b production (P = 0.022). Possession of allele 2 was also associated with significantly shorter survival (median 144 vs 256 days, P = 0.034) and significantly higher CRP level (P = 0.0003). The possession of a genotype resulting in increased IL-1b production was associated with shortened survival and increased serum CRP level. This may reflect the role of IL-1b in inducing an acute phase protein response and cachexia in cancer or may be related to changes in tumour phenotye. © 2000 Cancer Research Campaign http://www.bjcancer.com